-7(-6+9f)+3=

Simple and best practice solution for -7(-6+9f)+3= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(-6+9f)+3= equation:


Simplifying
-7(-6 + 9f) + 3 = 0
(-6 * -7 + 9f * -7) + 3 = 0
(42 + -63f) + 3 = 0

Reorder the terms:
42 + 3 + -63f = 0

Combine like terms: 42 + 3 = 45
45 + -63f = 0

Solving
45 + -63f = 0

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '-45' to each side of the equation.
45 + -45 + -63f = 0 + -45

Combine like terms: 45 + -45 = 0
0 + -63f = 0 + -45
-63f = 0 + -45

Combine like terms: 0 + -45 = -45
-63f = -45

Divide each side by '-63'.
f = 0.7142857143

Simplifying
f = 0.7142857143

See similar equations:

| 79-13= | | 9(-4z+5)-8= | | 3z^2-0.75=90 | | x+9=4(x-1)(x-1) | | 7+13x=11+13x | | 3(6x+8)=9x-16-x | | -8x-3=-48 | | 5x+2y=12findy | | y=x^2-2x-6y=4x+10 | | -16x^2+128x+2=0 | | (3x+2x+2+2x+2+5x+3)5= | | (-2x+3)(-x+15)=15 | | 2(x-6)=9-5x | | 6w-10w^3= | | (-2x)+(-x-16)=0 | | log(a)4=2 | | 3(x-2)=2x+2(x-8) | | 25(4-2x)=5(-6x) | | (5x-2)=(9x) | | -3(m+2)+6m=9(m+-1) | | 9a+33ab+-76b+65c+17a+51ab+-80b+13c= | | 3+16x+12=11x+15+5x | | -2c+3.7=-0.5 | | 21ab+-50b+13c+17a+30ab+-30b= | | 6x-42=9x | | 12x+2=12x-5 | | 9a+12ab+-26b+52c+21ab+-50b+13c= | | 7*4x=x+8 | | 8x-72=5x+25 | | 15ab+-24b+17a+15ab+-6b= | | 7x+14x+21x+28x=360 | | 94+84+62+y=(4-2)180 |

Equations solver categories